How Can Playfair Cipher Secure Data? - Azizah, Luthfi Nur (Proceeding International Conference on Science and Engineering, 2020)
Cryptography plays an important role in the digital world today. Information can be mathematically secured by the message sender with a key. The intended sender's privacy and recipient's information will be protected from eavesdroppers. The purpose of this paper is to find out how to secure data using a playfair cipher with a 16 X 16 matrix. This algorithm will provide the power to playfair cipher. The encryption and decryption process in cryptography uses keywords that have been agreed upon by the sender and recipient of the message. Entries of this matrix are large and small alphabet letters, numerical characters, and other special characters to construct the contents of the matrix. The characters refer to ASCII from 0 to 255.